The Effect of Perception of Convenience, Service Features, and Rewards on Reuse Interest - Diasafira, Elza; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
People nowadays are witnessing technological advancement in various areas; one of them is in finance through the emergence of non-cash payment services through electronic money or e-wallet, and DANA is one of providers. Although this company has succeeded in increasing the number of its users, complaints from them are also accumulating. There are many factors that can influence the intention of users to reuse a system, such as perceived ease of use, service feature, and rewards. The objective of this research is to examine the effects of perceived ease of use, service feature, and reward on the intention to reuse DANA. The population is active students in Malang City who use DANA. The sample of this quantitative explanatory research was selected through non-probability sampling methos and purposive sampling technique. The data was harvested via online questionnaires using Google Forms. The analytical process consists of validity test, reliability test, classical assumption test, multiple linear regression, and hypothesis testing, performed in SPSS. This study finds that all of its independent variables, i.e., perceived ease of use, service feature, and reward, positively and significantly influence the dependent variable, i.e., the intention of active students in Malang City to reuse e-wallet.